Endoscopic thyroidectomy to minimize light exposure of an erythropoietic protoporphyria patient: A case report. (June 2022) - Ishisaka, Tomo; Noda, Takuya; Shimode, Yuzo; Kitamura, Morimasa; Tsuji, Hiroyuki
Abstract: Introduction and importance: Erythropoietic protoporphyria is a rare form of cutaneous porphyria that presents with photosensitivity. During surgery, light shielding is required to prevent acute attacks due to photosensitivity. In this study, we report a case of successful endoscopic thyroidectomy using video-assisted neck surgery (VANS) method for a thyroid tumor in a patient with erythropoietic protoporphyria. Case presentation: A 32-year-old woman with a history of erythropoietic protoporphyria and an enlarged left thyroid gland was referred to our hospital. The referring physician had noted a left lobe tumor of the thyroid gland with a maximum diameter of 5 cm. Computed tomography and ultrasonography showed the tumor shape as smooth and well-defined. A lobectomy of the thyroid gland was performed using the VANS method through a 3-cm incision on the skin. Surgical light was not used and exposure to ambient light was minimized by covering the patient's neck with a drape. No acute attack of porphyria or photosensitivity was observed during the surgery or the follow-up. Postoperative complications such as asphyxia, blood loss, or nerve palsy were absent. The patient was discharged 5 days after the surgery. Clinical discussion: While the VANS method is known to have mainly cosmetic advantages, this case demonstrates that it is also a method that can minimize the exposure of the patient's skin to light with using an additional drape. Conclusion: The VANS method should be considered as an option for thyroidectomy in patients with protoporphyria because it can reduce the exposure to light during surgery. Highlights: A case of thyroid tumor with erythropoietic protoporphyria Exposure of patient's skin to light should be minimized. The VANS method can be chosen to reduce light exposure during surgery.